The Effectiveness Of Inhaled Corticosteroids In Reducing Exacerbations In Children With Moderate To Severe Asthma: A Systematic Review (The Review of Diabetic Studies, 2025)
Background: Asthma is a prevalent chronic respiratory condition in children, with exacerbations being a major cause of morbidity and healthcare utilization. Inhaled corticosteroids (ICS) are the cornerstone of anti-inflammatory treatment for persistent asthma. This systematic review evaluates the effectiveness of ICS in reducing exacerbations specifically in children with moderate to severe asthma.Methods: A systematic review was conducted following PRISMA 2020 guidelines. A comprehensive search of electronic databases (PubMed, Scopus, Cochrane Library, etc.) was performed for studies published from January 2000 to April 2025. Eligible studies included children aged 0–18 years with moderate to severe asthma, comparing ICS (monotherapy or combination therapy) against placebo, standard care, or alternative regimens, with outcomes on exacerbation frequency, hospitalization, or symptom control. Eight studies (seven RCTs, one retrospective cohort) involving 2,610 children were included after screening. Data were extracted and synthesized narratively due to heterogeneity.Results: All eight included studies demonstrated that ICS significantly reduce the frequency, duration, and severity of asthma exacerbations. Nebulized and metered-dose ICS formulations (budesonide, fluticasone, beclomethasone) were effective across all pediatric age groups, from infancy to adolescence. ICS use led to shorter hospital stays, increased symptom-free days, and improved lung function. Studies comparing different ICS agents found them to be therapeutically equivalent. Combination therapy with ICS and long-acting beta-agonists (LABA) was found to be superior to ICS monotherapy in reducing exacerbation incidence and severity in a long-term study.Conclusion: Inhaled corticosteroids are highly effective in reducing exacerbations in children with moderate to severe asthma. They consistently improve symptom control, reduce hospitalizations, and demonstrate a favorable safety profile. This review reaffirms ICS as the foundational controller therapy, with ICS/LABA combination offering enhanced benefit for more severe cases, supporting current evidence-based treatment guidelines.